Managing Short Course Initiatives for the Professional Development of Early Career Lecturers in Islamic Religious Universities - Devi Pramitha; Bunga Aprilia Firdausi (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to examine and analyze the management of the Early Career Lecturer Competency Improvement Program (PKDP) in fostering the professionalism of faculty members within the Directorate of Islamic Higher Education at the Ministry of Religious Affairs of the Republic of Indonesia. The focus of the analysis is on three key aspects of program management: planning, implementation, and evaluation. The research adopts a descriptive qualitative approach, wherein the researcher provides an in-depth exploration of the phenomenon under study. Data collection methods employed include observations, interviews, and document analysis. The collected data are processed through stages of data condensation, presentation, and conclusion drawing. To ensure data credibility, triangulation of sources and techniques is utilized. The findings indicate that the management of the PKDP for improving the competence of novice lecturers involves: (1) Planning, which is coordinated through meetings between government representatives and participating universities; (2) Implementation, which comprises two primary activities: the In-Service Course and On-the-Job Course; and (3) Evaluation, which is conducted through surveys and reporting mechanisms aimed at refining and enhancing the program for future iterations